Teaching and research in contemporary higher education : systems, activities and rewards - Shin, Jung Cheol; Arimoto, Akira; Cummings, William K; Teichler, Ulrich (New York : Springer, 2014)
This book discusses how teaching and research have been weighted differently in academia in 18 countries and one region, Hong Kong SAR, based on an international comparative study entitled the Changing Academic Profession (CAP). It addresses these issues using empirical evidence, the CAP data. Specifically, the focus is on how teaching and research are defined in each higher education system, how teaching and research are preferred and conducted by academics, and how academics are rewarded by their institution. Since the establishment of Berlin University in 1810, there has been controversy on teaching and research as the primary functions of universities and academics. The controversy increased when Johns Hopkins University was established in 1876 with only graduate programs, and more recently with the release of the Carnegie Foundation report Scholarship Reconsidered by Ernest L. Boyer in 1990. Since the publication of Scholarship Reconsidered in 1990, higher education scholars and policymakers began to pay attention to the details of teaching and research activities, a kind of black box because only individual academics know how they conduct teaching and research in their own contexts.
Introduction: Teaching and Research in Contemporary Higher Education: An Overview; Cummings and Shin -- PART I. Theoretical Basis -- 2. The Teaching and Research Nexus in the Third Wave Age; Arimoto -- 3. The Research Role in Comparative Perspective; Cummings -- 4. Teaching and Curriculum Development across Countries; Huang -- PART II. Research Focused Systems -- 5. Teaching and Research in Germany: The Notions of University Professors; Teichler -- 6. Teaching and Research at Italian Universities: Continuities and Changes; Rostan -- 7. The Changing Balance of Teaching and Research in the Dutch Binary Higher Education System; De Weert and Van der Kaap -- 8. The Scholarly Question in Finland: to Teach or not to Teach; Aarrevaara, Dobson and Postareff -- 9. Teaching and Research: perspectives from Portugal; Santiago, Sousa, Carvalho, Marchado-Taylor and Dias -- 10. Teaching and Research of Korean Academics across Career Stages; Shin, Jung and Kim --PART III. Teaching Focused Systems -- 11. The Divergent Worlds of Teaching and Research among Mexican Faculty: Tendencies and Implications; Galaz-Fontes, Martinez-Stack, Estevez-Nenninger, Padilla-Gonzalez, Gil-Anton, Sevilla-Garcia and Arcos-Vega -- 12. Research and Teaching in a Diverse Institutional Environment: Converging Values and Diverging Practices in Brazil; Schwartzman and Balbachevsky -- 13. Current Challenges Facing the Academic Profession in Argentina: Tensions between Teaching and Research; Leal and Marquina -- 14. Teaching and Research in Malaysian Public Universities: Synergistic or Antagonistic?; Azman, Pang, Sirat and Yunus -- 15. From Teachers to Perfect Humboldtian Persons to Academic Superpersons: The Teaching and Research Activities of the South African Academic Profession; Wolhuter -- PART IV. Teaching and Research Balanced Systems -- 16. The Balance between Teaching and Research in the Work Life of American Academics; Finkelstein --17. Teaching and Research in English Higher Education: The Fragmentation, Diversification and Reorganization of Academic Work, 1992-2007; Locke -- 18. Teaching, Research and the Canadian Professoriate; Jones, Gopaul, Weinrib, Metcalfe, Fisher, Gingras and Rubenson -- 19. Australian Academics, Teaching and Research: History, Vexed issues and Potential Changes; Bentley, Goedegebuure and Meek -- Concluding Observations -- 20. Teaching and Research across Higher Education Systems: A Typology and Implications; Shin and Cummings -- 21. Teaching and Research: A Vulnerable Linkage?; Teichler and Arimoto.
Keywords: Education; Education, Higher; Education; International and Comparative Education; Higher Education; Sociology of Education; korkeakouluopetus; korkea-asteen koulutus; tutkimustyö; vertaileva kasvatustiede; kansainvälinen vertailu; kasvatussosiologia